TaMAPK4 Acts as a Positive Regulator in Defense of Wheat Stripe-Rust Infection - Wang, Bing; Song, Na; Zhang, Qiong; Wang, Ning; Kang, Zhensheng (Frontiers in Plant Science, 2018)
Highly conserved mitogen-activated protein kinase (MAPK) cascades regulate numerous plant processes, including stress and hormonal responses and innate immunity. In this research, TaMAPK4 was predicted to be a target of tae-miR164. We verified the binding and suppression of TaMAPK4 by co-expression in Nicotiana benthamiana. Transient expression analyses indicated that TaMAPK4 was localized in the cytoplasm and nucleus. TaMAPK4 transcripts increased following salicylic acid (SA) treatment and when host plants were infected with an avirulent race of the stripe rust pathogen. Silencing of TaMAPK4 by virus-induced gene silencing (VIGS) permitted increased colonization by the avirulent pathogen race. Detailed histological results showed increased Puccinia striiformis (Pst) hyphal length, hyphal branches, and infection uredinial size compared to the non-silenced control. SA accumulation and the transcript levels of TaPR1, TaPR2, and TaPR5 were significantly down-regulated in TaMAPK4 knockdown plants. Overall, these results suggest that TaMAPK4 plays a role in signaling during the wheat-Pst interaction. These results present new insights into MAPK signaling in wheat defense to rust pathogen.